Dosage Considerations for Canakinumab in Children With Periodic Fever Syndromes. Issue 3 (28th January 2019) - Zhuang, Luning; Chen, Jianmeng; Yu, Jingyu; Marathe, Anshu; Sahajwalla, Chandra; Borigini, Mark; Maynard, Janet; Burckart, Gilbert J.; Wang, Yaning
Abstract : Periodic fever syndromes are a group of rare diseases with a highly variable onset, yet limited treatment options are available for children at an early age. Canakinumab has been approved to treat patients with cryopyrin‐associated periodic syndrome, a periodic fever syndrome, and systemic juvenile systemic arthritis, with age cutoffs of 4 years and 2 years, respectively. In 2016, the US Food and Drug Administration (FDA) approved canakinumab, without an age restriction, for the treatment of three conditions of periodic fever syndromes, including familial Mediterranean fever, hyperimmunoglobulin D syndrome/mevalonate kinase deficiency, and tumor necrosis factor receptor‐associated periodic syndrome. This review discusses the pharmacokinetic (PK), efficacy, safety, and exposure‐response relationship of canakinumab and provides the rationale for dosage recommendation in children younger than 2 years of age with the three conditions of periodic fever syndromes. The approval of canakinumab for these pediatric patients addresses a critical unmet medical need.